Pengaruh Variasi Ketebalan media Filtrasi Sistem Up-Flow Terhadap Kadar Fe, Mn, dan Kekeruhan Air Sumur Galu di RT 08 RW 02, Ngampilan, Kota Yogykarta - Habibah Nur Rahmatika; Purwanto Purwanto; Narto Narto (Sanitasi: Jurnal Kesehatan Lingkungan, 2015)
Water is the most important substance for life. Clean water should comply health requirements both in terms of the quality and the quantity. Clean water has to fulfill the quality regulated by the Ministry oh Health’s decree No. 416 in 1990 about physical, chemical, microbiological and radioactivity conditions. Some chemical and physical requirements for clean water are: the maximum thresholds for: Fe concentration 1 mg/l, Mn concentration 0,5 mg/ and turbidity 25 NTU. A preliminary study conducted at RT 08 RW 02, in Ngampilan of Yogyakarta City, found that a dig well water there was containing Fe of 4,8 mg/l, Mn of 0,6 mg/l and turbidity of 2185 NTU, which were exceeding the permitted limits. The study was aimed to know the influence of variations in the thickness of filtration media, i.e. quartz sand, activated charcoal and zeolite with up-flow system for the concentration reduction of Fe, Mn and turbidity in that area. There were three thickness variations used in the study, namely: Filter A (10 cm, 20 cm and 50 cm), Filter B (20 cm, 20 cm and 40 cm) and Filter C (30 cm, 30 cm and 20 cm), and an experiment with pre-test post-testwith control group design were conducted with five replications. The study data were analysed by one way anova and LSD tests at 0,05 significance level. The results showed that Filter B which consisted of 20 cm quartz sand, 20 cm activated charcoal, and 40 cm zeolite, was the most effective filter that was able to reduce 82,12 % Fe, 73 % Mn and 63,6 % turbidity.